Analisis Faktor-Faktor Pekerjaan Proyek Prasarana Jalan Lingkungan Kelurahaan Sukma Jaya Kecematan Sukma Jaya Kota Depok - Wennas Alau; Sempurna Bangun; Kristina Sembiring (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
The factors that can affect the delay in the completion of road construction projects within the government of the Depok City Public Works Agency which are obtained from the analysis are poor material procurement; insufficient human resources; less than optimal contract management; procurement of construction equipment that is not managed; there is a request for changes to the work being done; financial problems; poor construction work monitoring and control; negative intervention from the community; slow decision making by the owner and changes in field conditions (weather, accidents, etc.). Based on the relative index method, the most influential factors are: 1. Unmanaged procurement of construction equipment 2. Changes in field conditions. Meanwhile, in the factor analysis method, it is obtained: Inadequate human resources (in the form of quantity and quality) less incompatible with the existing location of activities CCO (Contract Change Order) often occurs.